Consumo como experiência social: experimentações, vivências e práticas da cultura pop em um coletivo juvenil - Brandão, Deyse de Fátima do Amarante. (2015)
This research aims to focus on the manifestations and social experiences around the young participants of Studio Made In PB, an existing collective in the city of João Pessoa (PB), since 1998, responsible for product, conduct and disseminate activities related to the pop culture in the city. As a term given by the participants of the research, pop culture propels collective and individual actions, revealing authentic and diverse coping mechanisms by such social actors that by appropriating themselves of the purchase of these goods reveal throughout the city lifestyles, identity constructions and group maintenance. By refining the look on the group's activities, the approach followed an ethnographic perspective having as the methodology the actions lived in the field’s work, interviews, informal conversations, virtual community interactions (Facebook) and imagistic registers with the members of the Studio Made In PB. By understanding the consume as a creator social practice, this research reflected on the consumer's role as active - and fandom, teacher, student, creator, staff - exercising strategic positioning on goods choices that open inventive possibilities, maintaining its own social dynamics. Emphasizing the Studio Made In PB as part of the manifestations of youth culture in João Pessoa, the analysis of this research allowed to know the recognition codes construction processes with other social groups in one of the most important activities of the group before their peers: the event "HQPB: comics and pop culture in Paraíba", that took place in November 2014. Above all, ethnographic research, that lasted almost 18 months, sought to understand these actors within the context of postmodern condition, in which they, even involved in complex games of signs in the ways of consumption, legitimize its provisions among themselves and among their peers, consolidating or reinforcing the bonding around the pop culture